The Third Generation (UMTS) Spectrum Auction in Germany - Veronika Grimm; Frank Riedel; Elmar G. Wolfstetter (Center for Economic Studies and ifo Institute (CESifo), 2001)
The third generation UMTS auction in Germany raised an enormous amount of revenue, and at the same time achieved a more competitive market structure than other UMTS auctions in Europe. The present paper explains the design of that auction, and presents a game theoretic explanation of observed events during the crucial phase of that auction, which have puzzled several observers. In addition, the paper evaluates the merit of the German UMTS auction design, relative to the English design, that was predominantly employed in Europe.
Keywords: 330; auctions; telecommunications; industrial organization; game theory.